Role of Open and Distance Learning (ODL) Education in Empowerment of Youth - Nasim Khan Mahsud (International Islamic University Islamabad, 2018)
The main purpose of the study is to examine the role of open and distance learning educational system in empowerment of youth in Pakistan. For the present study, 120 respondents both male and female students of post-graduate programs were recruited through purposive sampling technique. Survey method was used as a technique for data collection. A wellstructured questionnaire was administered to collect information from respondents attending workshops at AllamaIqbal Open University main campus Islamabad. The study showed that ODL is playing very important role in providing education and enhancing youth’ empowerment in especially this three areas, individual autonomy, socio-cultural and economic spheres. It is recommended that curriculum may also be competent enough to meet the futuristic and modern day educational and professional needs of the youth.